Immobization [sic] of activated carbon on fungal biomass for decolorization of textile mill wastewater - Khan, Mohammad Jakir Hossain (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
Availability and adsorptive properties are the main criteria for choosing the biosorbent to remove organic compounds from wastewater. Considering these criteria, an active biosorbent was prepared by immobilizing the commercial activated carbon with the fungal biomass through the fermentation process. The potential strains were selected based on immobilization capability through the screening test of different types of fungi. It was observed that the strains Aspergillus niger and Penicillium sp were able to immobilize 100% activated carbon with its biomass. The suitable pH and agitation rate for immobilization were pH 5 and 140 rpm. The percentage of produced biomass by Aspergillus niger and Penicillium sp was 88% and 75% respectively in immobilization process. The activated carbon immobilized on biomass (ACIB) as an active biosorbent were characterized by elemental analysis, surface techniques scanning electron microscopy (SEM) and Fourier transformer infrared spectroscopy (FT-IR). The functional groups of the biosorbent were observed by FT-IR. The results showed that ACIB gained more functional groups compared to the activated carbon used and particle size was reduced. For activated carbon, the average particle size was 43.9 μm whereas for immobilized activated carbon by Aspergillus niger and Penicillium sp was 7.9 μm and 8.4 μm respectively. Surface area of activated carbon was drastically decreased due to immobilization. The surface area of activated carbon was 697.1 m2/g, whereas immobilized activated carbon by Aspergillus niger showed was the surface area 26.11 m2/g and by Penicillium was 45.5 m2/g. The study on the adsorption of dyes showed significant removal of color in aqueous solution. From the adsorption study the Reactive Black R-150 was the best to be decolorized with biosorbent loading 15 g/L. The optimization study on Batik effluent showed that the residual concentration was 6.03 mg/L (removal about 80% dye) and 7.57 mg/L at pH 12, contact time 30 min and biosorbent dosages 12.5 gm/L. The study shows that the new ACIB material might be suitable for the removal of toxic dyes from the industrial wastewater.